2012
DOI: 10.1002/anie.201205126
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and Graphene Oxide Can “Lubricate” Ionic Liquids based on Specific Surface Interactions Leading to Improved Low‐Temperature Hypergolic Performance

Abstract: Space-qualified lubricants: Graphene and graphene oxide (r-GO) can strongly improve the low-temperature performance of hypergolic ionic liquids by reduction of viscosity. Key to success is to match the graphene type to the specific ionic-liquid functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…It has been shown [45] that IL molecules interact with graphene nanophases, producing new dispersions with a remarkable change in the physical properties of the nanofluid with respect to pristine IL. Low concentration stable graphene dispersions in IL can reduce the viscosity by reducing the internal friction between molecules and the cation-anion interactions.…”
Section: Ionanocarbon Lubricantsmentioning
confidence: 99%
“…It has been shown [45] that IL molecules interact with graphene nanophases, producing new dispersions with a remarkable change in the physical properties of the nanofluid with respect to pristine IL. Low concentration stable graphene dispersions in IL can reduce the viscosity by reducing the internal friction between molecules and the cation-anion interactions.…”
Section: Ionanocarbon Lubricantsmentioning
confidence: 99%
“…The combination of XPS, IR, and zeta potential results showed that strong interactions exist between boron and ionic liquids, in which a strongly bound layer that is dense enough to protect the boron surfaces from air oxidation exists on the surface of boron nanoparticles 23. In addition, others have demonstrated that the dispersions of graphene or graphene oxide in the hypergolic ionic liquids can significantly depress the viscosities of ionic liquids, thereby leading to improved lower temperature hypergolic performance but with a concomitant small increase in the ignition delay time 24. More interestingly, the type of graphene surface can lead to dramatically different viscosity and ignition behavior.…”
Section: Boron Chemistry: New Opportunity For Hypergolic Ionic Liquidmentioning
confidence: 99%
“…[23] In addition, others have demonstrated that the dispersions of graphene or graphene oxide in the hypergolic ionic liquids can significantly depress the viscosities of ionic liquids, thereby leading to improved lower temperature hypergolic performance but with a concomitant small increase in the ignition delay time. [24] More interestingly, the type of graphene surface can lead to dramatically different viscosity and ignition behavior. Essentially, the role of graphene-based nanomaterials in this strategy is the catalytic burn rate enhancer during the hypergolic reaction.…”
Section: Boron Chemistry: New Opportunity For Hypergolic Ionic Liquidmentioning
confidence: 99%
“…The current choices of hypergolic liquid propellants are primarily focused on hydrazine and its derivatives, such as monomethyl hydrazine (MMH) and unsymmetrical dimethylhydrazine (UDMH). However, these hydrazine‐based fuels are highly toxic owing to their volatility and carcinogenic properties, which leads to expensive storage and handling procedures and costly safety precautions . Hence, the search for more environmentally friendly hypergolic fuels has become a necessity for space science …”
Section: Introductionmentioning
confidence: 99%